Vertane Chancen? Die aktuelle politische Debatte um Erweiterte DNA‐Analysen in Ermittlungsverfahren - Lipphardt, Veronika (2018)
Abstract: Wasted Chances? The Current Political Debate on DNA Phenotyping and Biogeographical Ancestry Analysis in Criminal Investigation in Germany. This paper discusses diverse understandings of ‘responsible science’ in heated political debates. It takes a current public debate around a German law amendment draft concerning the use of novel forensic genetic techniques, namely DNA‐phenotyping and biogeographical ancestry analysis, as an example. A distinction is being made between an understanding that emphasizes scientific debate and precision, and another one that focuses on political agency. The paper also addresses the question whether and how science studies scholars, given their depth of expertise in the analysis of complex problems spanning disciplinary boundaries, should contribute to national debates in policy fields where no such dialogue exists yet